Modification of Two Algorithms Playfair And Caesar Chiper Al-gorithm Using Postal Code City: Modification of Two Algorithms Playfair And Caesar Chiper Al-gorithm Using Postal Code City - Sewindu Putro; Sumbogo Wisnu Pamungkas; Dony Ariyus (Institute of Computer Science (IOCS), 2020)
Privacy and data security is one of the most important aspects that need to be addressed, especially in this digital age where all desktop and mobile computing devices can be connected to one another in a virtual world that causes virtually impossible to protect the message to its destination. The purpose of this study is a modification of the Playfair cipher algorithm and caesar cipher with the postal code of the city, aims to produce a ciphertext that is more complex and not easily solved. In this penelian also implement LSB steganography method so that the message content more secure and not readily known by those who do not have an interest. From the test results of this study showed that by modifying the Playfair cipher algorithm and caesar cipher with city postal code in the encoding, produce ciphertext more complicated to be returned to the original message by parties who have no interest. Applying LSB steganography method makes the observer is not aware of the information that is pasted on the image that acts as a message.